The effect of self-management education following mild stroke: an exploratory randomized controlled trial*. Issue 5 (4th July 2017) - Wolf, Timothy J.; Spiers, Meredith J.; Doherty, Meghan; Leary, Emily V.
Abstract: Background : Mild stroke comprises 53% of stroke hospital admissions; however, the majority of those with mild stroke patients receive little support to address chronic symptoms following stroke. Objectives : To evaluate the feasibility and preliminary effect of the Chronic Disease Self-Management Program (CDSMP) for use with individuals immediately post mild-stroke. Methods : Single-blind, exploratory, randomized controlled trial with participants who sustained a mild stroke (NIHSS <6). Participants were randomized to either receive the CDSMP intervention or to an inactive control group. Primary outcomes were self-reported health and self-efficacy and were obtained at baseline, post-intervention (treatment group only), and at six months post-baseline. Wilcoxon Signed Rank Tests were used to compare change score differences for all participants and effect size was computed using effect size r for non-parametric data. Results : There were no differences between groups in demographics or baseline data with the exception of how participants felt they are able to manage their health in general ( p = 0.05). At follow-up, effect sizes ranged from 0 to 0.35 (no effect to medium effect); however, while the treatment group reported improvements in several areas of health at follow-up, the results are not compelling when compared to the control group over the same time period. Conclusions : The results did not identify a positive effect that would support the use of the CDSMP with individual's post-mild stroke; however, the generalizability of these results is limited secondary to several limitations in this exploratory study.